E-NTPDases: Possible Roles on Host-Parasite Interactions and Therapeutic Opportunities - Paes-Vieira, Lisvane; Gomes-Vieira, André Luiz; Meyer-Fernandes, José Roberto (Frontiers in Cellular and Infection Microbiology, 2021)
Belonging to the GDA1/CD39 protein superfamily, nucleoside triphosphate diphosphohydrolases (NTPDases) catalyze the hydrolysis of ATP and ADP to the monophosphate form (AMP) and inorganic phosphate (Pi). Several NTPDase isoforms have been described in different cells, from pathogenic organisms to animals and plants. Biochemical characterization of nucleotidases/NTPDases has revealed the existence of isoforms with different specificities regarding divalent cations (such as calcium and magnesium) and substrates. In mammals, NTPDases have been implicated in the regulation of thrombosis and inflammation. In parasites, such as Trichomonas vaginalis, Trypanosoma spp., Leishmania spp., Schistosoma spp. and Toxoplasma gondii, NTPDases were found on the surface of the cell, and important processes like growth, infectivity, and virulence seem to depend on their activity. For instance, experimental evidence has indicated that parasite NTPDases can regulate the levels of ATP and Adenosine (Ado) of the host cell, leading to the modulation of the host immune response. In this work, we provide a comprehensive review showing the involvement of the nucleotidases/NTPDases in parasites infectivity and virulence, and how inhibition of NTPDases contributes to parasite clearance and the development of new antiparasitic drugs.